Religión y política en Grecia: Temístocles y el oráculo de Delfos (Minerva, 2019)
After a brief introduction which highlights the close connection between religion and politics in Greece, the author starking from Plutarch and bearing in mind the testimony of Herodotus analyses the role of religion in the propaganda around the figure of Themistocles. According to the reading of the oracles dictated by Apollo in Hdt., VII 140 and 141 and to Themistocles political relations with the Spartans and Delphi in the period before and after Salamis, the author is inclined to situate the first oracle before Tempe and the second afterwards, arguing for Themistocles' manipulation of then so as to adjust them to the requirements of the events.